An experimental investigation of performance and instabilities of the R744 vapour compression rack equipped with a two-phase ejector based on short-term, long-term and unsteady operations. (25th February 2021) - Haida, Michal; Palacz, Michal; Bodys, Jakub; Smolka, Jacek; Gullo, Paride; Nowak, Andrzej J.
Highlights: A R744 refrigeration test rig for enhanced ejectors evaluation. A short-term system indicators analysis for subcritical and transcritical conditions. A system stabilisation improvement during long-term and unsteady operations. The best system control for pressure lift below 4 bar at subcritical conditions. The best system control for pressure lift above 4 bar at transcritical conditions. Abstract: In the case of R744 refrigeration technology, the system equipped with a two-phase ejector is one of the most efficient refrigeration systems, allowing utilisation of an R744-based unit in hot and tropical climates. However, the experimental analyses of the ejector-based system have only been performed for system performance evaluation, mapping the performance of ejectors or validation of the ejector numerical simulation. Therefore, the main goal/scope of this paper is to enhance the experimental knowledge of the state-of-the-art R744 vapour compression rack equipped with an efficient two-phase ejector, the relationship between the ejector and other components, and the influence of unsteady system work on the ejector performance and cooling demand. The test campaign was carried out on the R744 ejector-based test rig with a cooling capacity of 50 kW, high-side pressures from 60 bar to 100 bar and temperatures from 15 °C to 40 °C. The experimental analysis was conducted for three different system operating conditions, namely, short-term, long-term, and unsteady-state conditions, for refrigeration and air-conditioning applications. Utilisation of the ejector influenced the system instability, especially at the internal heat exchanger control. In addition, the low-pressure lift below 4 bar allowed the most efficient control strategy of the cooling demand for the operation below the critical point. For the transcritical unsteady operation, the most efficient operation was obtained for the defined pressure lift of 6 bar.